Penerapan Model Pembelajaran Problem Based Learning Pada Mata Pelajaran PKN Kelas 4 di SDN 1 Jatimerta - Apriyani (GENFABET: Generasi Pendidikan Dasar, 2025)
This study aims to analyze the Problem Based Learning (PBL) learning model in student learning confidence in Civics Education (Civics) subjects in elementary schools. The background of this research is based on the low participation of students in the Civics learning process which tends to be passive. The method used is a descriptive qualitative approach with data collection techniques in the form of semi-structured interviews with classroom teachers, observation of the learning process, and supporting documentation. The results showed that the application of PBL was able to encourage students to be actively involved in learning through group discussions, real problem solving, and presentation of work results. Students look more enthusiastic, critical, and show improvement in communication and collaboration skills. The application of PBL also provides space for students to develop higher order thinking skills needed in the 21st century. The conclusion of this study states that the PBL model is effective in increasing student learning activeness, especially in Civics subject. This research contributes to the development of innovative learning strategies that are relevant to be applied at the basic education level.